(untitled) (Research, Society and Development, 2020)
Bacaba (Oenocarpus distichus Mart) is a fruit that comes from palm trees native from the Arecaceae family and presents important nutritional and socioeconomic value for rural communities. Although being very popular, this fruit has very few cataloged chemical characteristics. The present study aimed to optimize the bacaba antioxidant extraction process by investigating the most efficient extraction interval and the best rotation time, using ethanol and methanol/acetone solvents, with the content of total phenolics and antioxidant activity. Methanol acetone solvent mixture was the most efficient solvent for extracting antioxidants from bacaba, with an extraction time of 90 minutes and 20 minutes of rotation interval at 5,000 rpm.